Abortion From Countries A to U: A Comparative Analysis of Abortion Laws and Attitudes in America and Uzbekistan - Heller, Thomas Allan (Medicine, Law & Society, 2024)
This paper compares and analyses abortion laws in the United States, one of the world’s oldest democracies, to those in Uzbekistan, an ancient middle Asian country that gained its independence from the Soviet Union in 1991. The authors examine both the United States and Uzbekistan constitutions and other laws regulating abortion and other reproductive rights. Regarding the United States, it tracks key abortion decisions from the Supreme Court. The authors also explore general attitudes about abortion and reproductive rights in both countries.